PENGARUH KINERJA PEGAWAI TERHADAP KUALITAS PELAYANAN DI PUSKESMAS KECAMATAN LEMBEH UTARA KOTA BITUNG - MANANEKE, TRIO; RARES, JOYCE; TAMPONGANGOY, DEYSI (JURNAL ADMINISTRASI PUBLIK, 2019)
One of the factors that becomes the criteria for achieving the smooth purpose of anorganization or agency is identifying and measuring the performance of its employees. all organizations arerequired to be able to compete to provide maximum service, performance achievements can be seen fromthe ability of organizations to recognize community needs, set the agenda and priority of services and developpublic service programs in accordance with the needs and aspirations of the community. There are twovariables in this study, namely variable employee performance (X) and service quality variables (Y). Thepurpose of this study was to determine the effect of employee performance on service quality in the HealthCenter of North Lembeh District, Bitung City. In this study the method used is a quantitative method. Datacollection techniques used were observation and distribution of questionnaires or questionnaires distributedto forty respondents. The results of the validity and reliability tests show that each item is valid and reliable.Then from the results of simple linear regression analysis it is found that every 1% increase in the value ofthe employee performance variable, the value of the service quality variable increases by 0.500 and it canbe said that the direction of the influence of employee performance on service quality is positive.Keywords: Performance, Employees, Service Quality